Exploring risk factors for comorbid depression in osteoarthritis: a scoping review protocol - Markus Ritter; Wolfgang Hitzl; Antje van der Zee-Neuen; Bibiane Steinecker-Frohnwieser; Kathrin Maria Bogensberger; Dagmar Schaffler-Schaden; Eva Perl (BMJ Open)
Introduction Globally, osteoarthritis (OA) is the most prevalent musculoskeletal disease, affecting approximately 600 million people. It is characterised by progressive degeneration of the articular cartilage, osteophyte formation and asymmetric joint space narrowing, leading to pain, stiffness and functional impairment. The current focus of disease management is on symptom relief and functional improvement. However, these interventions frequently do not provide adequate outcomes. This may be attributed to a lack of consideration for contextual factors, including the presence of comorbidities such as depression. Several studies indicate that depression is highly prevalent, affecting up to 20% of patients with OA. As depression is known to be a multifactorial disorder, there are various risk factors that may increase the likelihood of comorbid depression in patients with OA. Consequently, the scoping review’s objective is to map the existing literature on risk factors for comorbid depression in individuals with OA. Furthermore, the review is expected to provide important information for further in-depth investigation and the development of predictive tools to support the early identification of patients with OA at risk of comorbid depression.Methods and analysis The intended review will target studies reporting risk factors for comorbid depression in individuals with OA. All available primary and grey literature will be considered for inclusion. Only articles published in English or German will be included in the review. The review will follow the format specified by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews and the Joanna Briggs Institute Manual for Evidence Synthesis. Original research in published and unpublished literature from inception until August 2024 will be included in the review. The databases to be searched will include PubMed, EMBASE, PsycInfo and Web of Science. In addition, further literature will be identified by searching the reference lists of the included studies. Three reviewers will independently screen the identified studies for final inclusion. The data will be extracted and presented in tabular form and in a narrative summary that aligns with the review’s objective. Furthermore, a quality assessment of the included studies will be conducted using appropriate tools, and the results will be incorporated into the synthesis. Any disagreements that arise between the reviewers will be resolved through discussion or with an additional reviewer.Ethics and dissemination Ethics committee approval will not be required because only published and publicly available data will be examined to answer the research question of the scoping review. We will not collect any personal information or any information that requires ethical approval. Following the conclusion of the review, the information will be disseminated to clinicians, health administrators and researchers via publications in peer-reviewed journals and conference presentations.